Дистанційне навчання в системі медичної освіти (перший досвід кафедри нормальної фізіології ЗДМУ) - Кущ, Оксана Георгіївна; Омельянчик, Володимир Миколайович; Бессараб, Георгій Ігнатович; Жернова, Наталія Петрівна; Степанова, Надія Володимирівна; Тихоновська, Марина Анатоліївна; Морозова, Оксана Валентинівна; Сухомлінова, Ірина Євгенівна; Kushch, О. H.; Omelianchyk, V. M.; Bessarab, H. I.; Zhernova, N. P.; et al. (My University, 2017)
Мета роботи – дослідження доцільності впровадження масових відкритих онлайн-курсів у систему вищої медичної освіти. Основна частина. У даній статті поставлена проблема переходу вузів України від традиційного дистанційного навчання до масового електронного навчання на основі відкритих онлайн-курсів, обґрунтована її актуальність. Проведено аналіз найважливіших передумов для успішного переходу на даний вид навчання (затребуваність освітніх інтернет-ресурсів, які використовуються з мобільних пристроїв; наявність великої кількості різних електронних ресурсів, які успішно використовуються вузами на практиці в дистанційних освітніх технологіях; наявність досвіду ведення електронних журналів успішності студентів для планування й оцінювання результатів навчання). Визначені ключові завдання переходу до розробки онлайн-курсів. The aim of the work – to investigate the feasibility of massive open online courses introducing into the higher medical education system. The main body. The issue of higher education institutions of Ukraine transition from traditional distance learning to massive electronic education on the basis of the online open courses is considered, its relevance is proved. Analysis of the major prerequisites for transition success is carried out (a demand for the educational Internet resources from mobile devices; existence of a large number of various electronic resources which are successfully used in practice by higher education institutions in remote educational technologies; maintaining experience for electronic magazines of students’ progress for planning and estimation of training results; essential growth of material costs in the world online training market). Key issues of transition are de􀂾 ned and the basic principles of electronic online courses development are formulated a technique for electronic online course development aimed as the result is given. The technique contains the following four stages: planning of expected training results, course electronic content structuring and training scenarios creation, development of the tests plan and electronic estimated means for automatic control of the planned training results, course realization by means of game mechanics and technologies of network communication between students. Requirements to various forms of control planned in the course of learning results are de􀂾 ned. Finally, the actual tasks of mass open education development in the leading higher education institutions of Ukraine are set forth.
Distance learning in the system of medical education
Keywords: електронне навчання; масова відкрита освіта; масові відкриті онлайн-курси; дистанційні освітні технології; інформаційні технології; система управління навчанням; соціальна мережа; e-learning; massive open education; massive open online courses; distance education technologies; information technologies; learning management system; social network